Fatores associados à iniciação sexual e reprodutiva na adolescência: um estudo para Belo Horizonte e Recife, 2002 - Marla Barroso Franca (2008)
This work aims to identify by discrete-time hazard models the factors associated with sexual initiation and fertility among teenagers based on the Reproductive Health, Sexuality, and Race Research (Saúde Reprodutiva, Sexualidade e Raça/cor - SRSR) carried out in Belo Horizonte and Recife in 2002. Education level and age were the factors associated with both final models. The variables age at menarche, race, and residence in slums correlated significantly with the occurrence of the first sexual intercourse. In the analysis of first childbearing in adolescence, besides education and age, only the use of contraceptives in the first sexual intercourse in adolescence showed an association with the risk of first childbearing in adolescence. From the viewpoint of public policies, only education is subject of intervention. In this study, adolescents with eight years of schooling or more had a risk of sexual intercourse or first childbearing in adolescence 60% lower when compared with young women with four or less years of schooling. Promoting education is an essential aspect to take into consideration in public policy for the sexual and reproductive health of teenagers.